Review—Aspects of Electrochemical Gas Sensor Technologies - Luke Saunders; Benjamin R. Horrocks (ECS Sensors Plus, 2025)
The use of electrochemical sensors for scientific study is widespread, and different types of electrochemical sensors are found throughout the world. In this review article we discuss the different technologies available to those using electrochemical sensors and consider the fundamental scientific principles that underpin their detection mechanisms. A brief consideration of the most common applications of electrochemical sensors is given and we discuss examples of the most common electrochemical analysis methods used by researchers to investigate such sensors. It is shown that electrochemical sensors can be powerful tools for scientific investigation and although there has already been much research into their operating mechanisms and usages, there is still plenty of exciting research areas to investigate in the future.